2021
DOI: 10.3389/fcell.2021.705697
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NEAT1 Promotes Gastric Cancer Progression Through miR-17-5p/TGFβR2 Axis Up-Regulated Angiogenesis

Abstract: BackgroundLong non-coding RNAs (lncRNAs) have been indicated to play critical roles in gastric cancer (GC) tumorigenesis and progression. However, their roles in GC remain to be further elucidated.MethodsRT-qPCR and fluorescence in situ hybridzation (FISH) were conducted to detect the expression of lncRNA NEAT1 in GC tissues and cell lines. Gene Set Enrichment Analysis (GSEA) was performed to screen out potential phenotypes and pathways that NEAT1 may participate in. NEAT1-silenced AGS and MGC803 cells were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
(45 reference statements)
2
19
0
Order By: Relevance
“…Here, we found that two lncRNAs (lncRNA-AC005005.4-201 and NEAT1-203) and two circRNAs (circRNA-hsa_HLA-B_1 and hsa_VEGFC_8) may regulate the inhibiting effects of hsa-miR-6747-3p for CSF3R expression, while lncRNA-DLX6-AS1-201 or circRNA-hsa_HLA-B_1 may neutralise the negative regulation of hsa- miR-4525 for GAA. Consistent with our findings for dysregulated lncRNAs in SCLC, previous studies found that lncRNAs DLX6-AS1 and NEAT1 were significantly dysregulated in non-SCLC, gastric cancer and pancreatic cancer (59)(60)(61)(62). Specifically, upregulated DLX6-AS1 in gastric cancer tissue associated with distant metastasis and a poor clinical prognosis, while siRNA-DLX6-AS1 may inhibit gastric cancer cell proliferation, migration, invasion and the epithelialmesenchymal transition in vitro (18).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Here, we found that two lncRNAs (lncRNA-AC005005.4-201 and NEAT1-203) and two circRNAs (circRNA-hsa_HLA-B_1 and hsa_VEGFC_8) may regulate the inhibiting effects of hsa-miR-6747-3p for CSF3R expression, while lncRNA-DLX6-AS1-201 or circRNA-hsa_HLA-B_1 may neutralise the negative regulation of hsa- miR-4525 for GAA. Consistent with our findings for dysregulated lncRNAs in SCLC, previous studies found that lncRNAs DLX6-AS1 and NEAT1 were significantly dysregulated in non-SCLC, gastric cancer and pancreatic cancer (59)(60)(61)(62). Specifically, upregulated DLX6-AS1 in gastric cancer tissue associated with distant metastasis and a poor clinical prognosis, while siRNA-DLX6-AS1 may inhibit gastric cancer cell proliferation, migration, invasion and the epithelialmesenchymal transition in vitro (18).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the other dysregulated lncRNA reports ( 59 62 ), Xu et al. found that lncRNA-NEAT1 may promote gastric cancer angiogenesis by enhancing the proliferation, migration and tube formation ability of endothelial cells through the miR-17-5p/transforming growth factor-β receptor 2 (TGFβR2) pathway ( 61 ), while lncRNA-NEAT1 may play a vital role in tumorigenesis and the development of SCLC through the hsa-miR-6747-3p/CSF3R axis. Importantly, in addition to lncRNA-DLX6-AS1 and NEAT1, we are the first to report another potential regulatory axis of ceRNA, while the regulatory mechanisms require further exploration through in vivo and in vitro studies.…”
Section: Discussionmentioning
confidence: 66%
“…With the use of a Wnt activator, the inhibitory effect of Lnc NEAT1 on EPCs function was partially alleviated. The phenomenon could be deciphered that Lnc NEAT1 participate in angiogenesis through multiple signaling pathways [ 56 58 ]. Yangwei Xu et al[ 56 ] demonstrated that LncRNA NEAT1 promoted gastric cancer progression through miR-17-5p/TGFβR2 axis up-regulated angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon could be deciphered that Lnc NEAT1 participate in angiogenesis through multiple signaling pathways [ 56 58 ]. Yangwei Xu et al[ 56 ] demonstrated that LncRNA NEAT1 promoted gastric cancer progression through miR-17-5p/TGFβR2 axis up-regulated angiogenesis. Lidong Zhao et al[ 57 ] also found that Lnc NEAT1 promoted trophoblast proliferation and invasion in gestational hypertension and alleviated vascular endothelial injury by inhibiting miRNA-205-5p.…”
Section: Discussionmentioning
confidence: 99%
“…MALAT1 is one of the most abundant lncRNAs in normal tissues, and emerging evidence has linked MALAT1 to lung cancer, breast cancer, prostate cancer, and pancreatic cancer [29]. In pancreatic cancer, importin 7 (a nuclear transport factor) inhibits the expression of p53 and induces the expression of MALAT1, resulting in the progression of pancreatic cancer [30]. LINC01963 is expressed at lower levels in pancreatic cancer tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%